Extramedullary hematopoiesis in ovary: a rare presentation of CML - Agarwal, Akriti; Gokhale, Asha Niranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Extramedullary hematopoiesis (EMH) is a rare phenomenon, and represents infiltration and proliferation of myeloid, erythroid, and megakaryocytic cells in non-bone marrow sites. Extramedullary hematopoiesis (EMH) is normal during fetal life, but after birth, the presence of EMH is considered to be abnormal. EMH has been associated with CML (chronic myeloid leukaemia). Lymph node is the most common site of involvement, other sites being the abdomen (liver, spleen) and thorax (bone, mediastinum) but very rarely in the gynecological tract. Here authors report a case of a 20-year young female, a known case of CML who presented with abdominal pain with hemoperitonium, with negative urine pregnancy test. Initially hemorrhagic corpus luteal cyst was thought to be the cause of hemoperitonium and patient was taken for surgery wherein histopathology confirmed the diagnosis of extra medullary hematopoiesis of ovary. Women with CML when presents with hemoperitoneum, extramedullary hematopoiesis should be a differential diagnosis apart from rupture ectopic and other causes of spontaneous hemoperitoneum. Patient was started on imatinib after diagnosis and is doing well.